Dynamics of Explosions in Cylindrical Vented Enclosures: Validation of a Computational Model by Experiments - Samuel Ogunfuye; Hayri Sezer; Furkan Kodakoglu; Hamed Farmahini Farahani; Ali S. Rangwala; V’yacheslav Akkerman (Fire, 2021)
Recent explosions with devastating consequences have re-emphasized the relevance of fire safety and explosion research. From earlier works, the severity of the explosion has been said to depend on various factors such as the ignition location, type of a combustible mixture, enclosure configuration, and equivalence ratio. Explosion venting has been proposed as a safety measure in curbing explosion impact, and the design of safety vent requires a deep understanding of the explosion phenomenon. To address this, the Explosion Venting Analyzer (EVA)—a mathematical model predicting the maximum overpressure and characterizing the explosion in an enclosure—has been recently developed and coded (Process Saf. Environ. Prot. 99 (2016) 167). The present work is devoted to methane explosions because the natural gas—a common fossil fuel used for various domestic, commercial, and industrial purposes—has methane as its major constituent. Specifically, the dynamics of methane-air explosion in vented cylindrical enclosures is scrutinized, computationally and experimentally, such that the accuracy of the EVA predictions is validated by the experiments, with the Cantera package integrated into the EVA to identify the flame speeds. The EVA results for the rear-ignited vented methane-air explosion show good agreement with the experimental results.